Натчези - високорозвинений індіанський народ Північної Америки - Балушок, В. (Народна творчість та етнографія, 2007)
Natchez, a Native American Tribe living down the Mississipi, was one of the most developed ethnic groups of North-America since the time of its discovery by Europeans. They were direct descendants of the magnificent Mississipian culture. The tribe enjoyed social stratification, mighty rulers whose power was sacred, a network of temples with numerous priests and human sacrifices, the cult of the sun and dead rulers. The Natchez reached the level of proto-state or early-state civilization.